Poetry for socio-political justice in Palestine: Mahmoud Darwish’s translation and re-narration of Palestinian–Israeli encounters - Alhirthani, Mahmoud (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
While Mahmoud Darwish’s work has been studied largely from a literary perspective, not much attention has been given to its translational dimensions. This article examines two of Darwish’s poems, “Identity Card” (1964) and “A Soldier Dreams of White Tulips” (1967), as two complementary endeavours aimed at achieving justice for the Palestinian people. It focuses on the socio-political contexts of their production, circulation, and reception to demonstrate the pivotal role translation as (re-)narration can play in the pursuit of justice and in challenging hegemonic narratives. Both poems became sites of political controversy due to the ways in which they were produced, translated, and re-narrated across languages and modalities. Whereas “Identity Card" offers a personal and public narrative of Palestinians’ confrontation with Israelis, “A Soldier Dreams of White Tulips” opens up a space in which to hear the remorse of an Israeli soldier at the acts of killing he committed against the poet’s own people. Unsurprisingly, the two poems were received very differently: “Identity Card” became a national poem in Palestine whereas “A Soldier Dreams of White Tulips” received little acclaim in the Arab world, being criticized because it stood against the pervasive public narratives of the 1960s according to which the humanized soldier portrayed by Darwish does not exist in the enemy’s camp. However, decades later, the poem has been proven right, as the soldier is revealed to be Shlomo Sand, the Israeli writer and activist, known for taking resolute steps towards justice and against Israeli mainstream narratives – to the extent that his work is translated into Arabic by Palestinian translators at the request of Darwish himself. It is in this new context that “A Soldier Dreams of White Tulips” is rediscovered decades after it appeared for the first time and becomes the object of temporal and spatial framing across contexts and modalities, including translations, recitations, and documentaries. At a time of despair arising from entrenched injustices and crimes against humanity perpetrated by Israel settler colonialism, the dynamics of the poem’s emergence and later revival may well inspire alternatives to existing hegemonic narratives of selves and others that continue to stand in the way of justice for the Palestinian people.